2000
DOI: 10.1038/sj.gt.3301295
|View full text |Cite
|
Sign up to set email alerts
|

Local administration of transcription factor decoy oligonucleotides to nuclear factor-κB prevents carrageenin-induced inflammation in rat hind paw

Abstract: The transcription factor nuclear factor-B (NF-B) plays a key role in the expression of several genes involved in the inflammatory process. In the present study we investigated in an acute model of inflammation, the carrageenin-induced hind paw edema, the anti-inflammatory effect of double stranded oligodeoxynucleotides (ODN) with consensus nuclear factor-B (NF-B) sequence as transcription factor decoys (TFD) to inhibit NF-B binding to native DNA sites. Local administration of wild-type, but not mutant-ODN deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…Although small DNA fragments (Ͻ50 bp) have been widely used as decoy and antisense molecules in vivo, [13][14][15]17,18 their biodistribution after topical administration to the lung has not yet been studied. We have shown that both 'naked' and lipid-complexed decoy ODN have similar biodistribution and subcellular localisation in the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although small DNA fragments (Ͻ50 bp) have been widely used as decoy and antisense molecules in vivo, [13][14][15]17,18 their biodistribution after topical administration to the lung has not yet been studied. We have shown that both 'naked' and lipid-complexed decoy ODN have similar biodistribution and subcellular localisation in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…NF B decoy oligonucleotides, which resemble consensus binding sites for NF B, and therefore inactivate the transcription factor have been used successfully in several inflammatory disease animal models. [13][14][15] We have previously demonstrated that NF B decoy oligonucleotides (ODN) reduced basal and LPS-stimulated IL-8 secretion in a CF airway epithelial cell line, 16 but their effect in models of pulmonary inflammation in vivo has not yet been investigated. We have, therefore, assessed the effect of NF B decoy ODN administration during the acute phase of bleomycininduced pulmonary inflammation in C57Bl/6 mice in vivo.…”
Section: Nuclear Transfection Significantly We Determined the Effectmentioning
confidence: 99%
“…On the other hand, the NF-κB targeting strategy includes: (a) blocking the DNA binding of NF-κB using decoy oligodeoxynucleotides (ODNs) [28]; (b) blocking the transactivation of NF-κB using glucocorticoids [93]; or (c) interfering with NF-κB mRNA using NF-κB antisense oligonucleotide (ASO) [43].…”
Section: Nf-κb Inhibition: Strategy For Cancer Therapymentioning
confidence: 99%
“…One mechanism is the use of a transcription factor decoy (TFD) peptide, called double-stranded oligodeoxynucleotide (ODN), that binds the same complementary region of specific DNA sites, competitively inhibiting NF-B binding. 207 Other examples of inhibi-…”
Section: Block Binding Of Nf-b To the Dnamentioning
confidence: 99%